PERTANGGUNGJAWABAN MANAJER INVESTASI TERKAIT WANPRESTASI YANG DILAKUKAN TERHADAP INVESTOR REKSA DANA KONTRAK INVESTASI KOLEKTIF DI DENPASAR - Prawira, Yudi; Wairocana, I Gusti Ngurah (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 07, Juli 2013, 2013)
Mutual fund is a place for lenders/investors to investment their funds intoportfolio by Investment Manager, in other words, the Investment Manager has animportant role in managing investors funds. Especially the funds which ismanaged by Investment Manager is huge, but the rules about it deemedinadequate caused the Investment Manager often did mistakes by ignoringInvestors right which is makes the investors loss and unprotected. The issues thatwill be discussed, how is the legal protection that given to mutual fund investorsand the responsibility of manager investment who did default to their investors.The legal research that used is empirical legal research by some interview. Fromit, shown the protection that given to investors is about openness ManagerInvestment information which is responsibility as any loss that investors get butno more than the fee that given by investors to the Manager investment.
Keywords: Responsibility, Defaults, Investors, Mutual Funds